Fearless : a Mirrorworld novel - Funke, Cornelia, 1958- (Funke, Cornelia, 1958- Reckless (Series)., 2013)
"Jacob Reckless journeys to the Mirrorworld to tell his shapeshifting friend Fox that a fairy curse--a deadly moth in his chest--means he has only one year to live. The journey in Mirrorworld turns into a search against time and against a Goyl treasure hunter for an enchanted crossbow, which is known to strike down any army it faces, and less well known for its healing power when shot by a loved one"--